2022
DOI: 10.3390/ijms23020645
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of Deep Eutectic Solvents: Challenges, Solutions, and Perspectives

Abstract: Deep eutectic solvents (DESs) are one of the most rapidly evolving types of solvents, appearing in a broad range of applications, such as nanotechnology, electrochemistry, biomass transformation, pharmaceuticals, membrane technology, biocomposite development, modern 3D-printing, and many others. The range of their applicability continues to expand, which demands the development of new DESs with improved properties. To do so requires an understanding of the fundamental relationship between the structure and pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 413 publications
(707 reference statements)
0
28
0
Order By: Relevance
“…For DES, these properties include phase behavior, melting temperature, density, conductivity, surface tension, viscosity, and polarity [ 48 , 57 , 73 , 74 ]. For DES application as a green extraction solvent, viscosity and polarity have been identified as the two DES properties that have large influence on the extraction performance [ 75 , 76 ]. One of the advantages of using DES is that its properties can be easily tailored by changing the type of DES components, the molar ratio between the components, and by water addition.…”
Section: Des As Extraction Solventmentioning
confidence: 99%
“…For DES, these properties include phase behavior, melting temperature, density, conductivity, surface tension, viscosity, and polarity [ 48 , 57 , 73 , 74 ]. For DES application as a green extraction solvent, viscosity and polarity have been identified as the two DES properties that have large influence on the extraction performance [ 75 , 76 ]. One of the advantages of using DES is that its properties can be easily tailored by changing the type of DES components, the molar ratio between the components, and by water addition.…”
Section: Des As Extraction Solventmentioning
confidence: 99%
“…There are some reviews that focus on simulations of DESs as a central topic. 166–168 Most of the applications are related to the interactions of DESs with different compounds and media. However, in some research fields, such as solubility studies with biomolecules and molecular mechanisms of the interactions between DESs and nanoparticles, there are currently very limited investigations.…”
Section: The Structural Stability and Activity Of Proteins In Dess Vi...mentioning
confidence: 99%
“…Nonpolarizable force fields were used in almost all MD simulations of the DES . Only recently have efforts been focused on polarizable ones. , The CL&Pol has the advantage of being a transferable polarizable model. As a result, the CL&Pol parameters are the obvious choice for parameters.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, various spectroscopic evidences and theoretical investigations using quantum chemistry calculations and molecular dynamics (MD) simulations have suggested that there is no single source of melting point drop in a DES. , The analysis of vibrational spectra obtained by infrared (IR), Raman, and inelastic neutron scattering (INS) spectroscopies have been particularly beneficial in revealing the intricate pattern of intermolecular interactions in a DES. Using as an example choline chloride/urea 1:2, which is the most studied DES, it has been shown in a combined study using IR, Raman, and INS, that, in addition to the HBA–HBD interaction, changes in the local structure and conformational flexibility of the molecules in comparison to the crystal structure and the formation of urea dimers in the liquid phase should all be considered as contributors to the reduction in the melting temperature . Owing to the occurrence of many interactions between the cation, anion, and molecular species, the use of classical or ab initio MD simulations , reveal the complex pattern of interactions and substantially assist the interpretation of vibrational spectra of a DES.…”
Section: Introductionmentioning
confidence: 99%